Antimicrobial Activity Testing of Ethyl Acetate Fraction from Mikania micrantha Leaves Against Escherichia coli and Staphylococcus aureus - Ivan Junius Mesak; Mariana Kristiani (Universitas STRADA Indonesia, 2025)
Bacterial infections remain a major global health issue, worsened by rising antibiotic resistance. This study evaluated the antimicrobial activity of the ethyl acetate fraction of Mikania micrantha leaves against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive) using the disc diffusion method. Phytochemical screening identified flavonoids, tannins, saponins, and steroid/triterpenoids in the fraction. The antimicrobial test showed that this fraction inhibited the growth of both bacteria, with larger inhibition zones observed at higher extract concentrations. At 5% concentration, E. coli showed an inhibition zone of 8.43 mm, while at 15%, the zone increased to 12.26 mm. For S. aureus, the 15% concentration produced a 20.43 mm inhibition zone. Statistical analysis confirmed significant differences between concentrations (p < 0.05). These results suggest that the ethyl acetate fraction of Mikania micrantha leaves has potential as an antibacterial agent, especially effective against Escherichia. coli at 15%.